Extraction of Cr (VI) from Aqueous Solution using Oil Palm waste impregnated with sulphuric acid - Naimah Ibrahim; Masitah Hasan; Salwa Mohd Zaini Makhtar; Nazzery Rosmady Rahmat; Khairul Nizar Ismail (Universiti Teknologi MARA (UiTM) & Advanced Materials Research Centre (AMREC) SIRIM Berhad, 2008)
Organized by Universiti Teknologi MARA (UiTM) & Advanced Materials Research Centre (AMREC) SIRIM Berhad, 29th May - 1st June 2007 at Hotel City Bayview Langkawi, Kedah.